Bandwidth and gain enhancement using nested cross-coupled positive feedback. (January 2019) - Kokabi, Alireza; Ghanbari Khorram, Hamidreza
Abstract: Using nested cross-coupled positive resistive feedback along with the positive capacitive feedback (PCF), a novel GBWP (gain × bandwidth) enhancement technique is proposed for the cascade amplifiers. An AC model of the proposed topology is also presented here to deliver the better understanding of the technique along with the behavioral comparison with the previous PCF-based amplifiers. The 300 GHz- f T SiGe technology has been considered here and it is shown that a bandwidth in the order of 116 GHz at the voltage gain of 27 dB is achievable. Here, we report several fascinating improvements such as 107% expansion in the bandwidth, 13.4 dB enhancement in the gain and 5.65 times boosting in the GBWP with respect to the previously reported TZCDP topology. Interestingly, the middle-band voltage gain of the proposed circuit is raised for the larger source resistances. Furthermore, the proposed three-stage cascade amplifier is capable of delivering a bandwidth which is 39% of its transistors transition frequency.